2015
DOI: 10.1186/s12989-016-0124-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution and acute toxicity of silver after single intravenous administration in mice: nano-specific and size-dependent effects

Abstract: BackgroundSilver nanoparticles (AgNPs) are an important class of nanomaterials used as antimicrobial agents for a wide range of medical and industrial applications. However toxicity of AgNPs and impact of their physicochemical characteristics in in vivo models still need to be comprehensively characterized. The aim of this study was to investigate the effect of size and coating on tissue distribution and toxicity of AgNPs after intravenous administration in mice, and compare the results with those obtained aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
176
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(194 citation statements)
references
References 65 publications
(116 reference statements)
11
176
0
1
Order By: Relevance
“…61,62 However, it has been concluded that deposition of AgNPs in tissue samples is sizedependent in the liver and kidneys of male and female rats. 63,64 In this study, Se treatment of AgNPs exposed rats showed alleviation of the histopathological changes in rat livers.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 However, it has been concluded that deposition of AgNPs in tissue samples is sizedependent in the liver and kidneys of male and female rats. 63,64 In this study, Se treatment of AgNPs exposed rats showed alleviation of the histopathological changes in rat livers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, coating has been reported to play an important role in NPs toxicity. In this context, in vivo studies have reported that polyvinylpyrrolidone (PVP) and citrate (CT) coated AgNPs induce tissue specific toxicity and aggravate cardiac ischemic reperfusion injury [20,21]. Moreover, a previous in vitro study has shown that PVPand CT-AgNPs induce toxicity in J774A.1 macrophage and HT29 epithelial cells [22].…”
Section: The In Vitro Effect Of Polyvinylpyrrolidone and Citrate Coatmentioning
confidence: 99%
“…The largest share of silver that reaches the blood is filtered by the liver and excreted through the gall. 7,9,15 The scheme of silver treatment has been described depending on the size in the liver and it has been suggested that absorption of silver by the Kupffer cells hardly occurs after administration of 100 nm AgNPs, while the introduction of 10 nm and 40 nm AgNPs led to the absorption of silver both endothelial cells and hepatocytes, in addition to the Kupffer cells. Only occasionally, silver was identified in gallbladder of 10 nm AgNP-treated mice (within the epithelial cells of the gallbladder and endothelial cells of blood vessels).…”
Section: Discussionmentioning
confidence: 99%
“…In lungs silver was found in the alveolar walls, capillaries, and interstitial tissue. 15 In literature, there are data about the impact of nanoparticles on oocytes. [16][17][18] There have been published data about the effect nanoparticles of gold, silver, and gold-silver alloy, which were covered with bovine serum albumin (BSA) on in vitro cumulus-oocytes-cellcomplexes of pigs.…”
Section: Discussionmentioning
confidence: 99%